(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Background: A novel corona virus disease known as COVID-19 has been declared a pandemic and a global health emergency by the WHO. The COVID-19 vaccination was first administered in India on January 16, 2021. India’s well-organized immunization program and high vaccination coverage are well-known internationally. Aim: To determine the level of knowledge with attitude regarding COVID-19 vaccination among adults in suburban areas of Mumbai Metropolitan Region. Methodology: This Non-experimental descriptive research design involved 359 adults using a self-structured questionnaire to assess knowledge and the standard VAX scale used to assess attitudes regarding COVID -19 vaccination. Results: A total of 359 adults participated in the study, out of the total participants 41% have average knowledge regarding COVID-19 vaccination (mean knowledge score= 14.39; SD=4.0), high knowledge scores associated with male gender, people who speak the local language and those who working as medical personnel at p-value